Addressing Labor Needs by Understanding Grower Perceptions about Adoption of Automated Nursery Technologies: A Resource for US Extension Professionals - Laura A. Warner; Alicia L. Rihn; Amy Fulcher; Susan Schexnayder; Anthony V. LeBude; Lloyd Nackley; Margarita Velandia; James Altland (EDIS, 2022)
This new 5-page publication of the UF/IFAS Department of Agricultural Education and Communication presents research assessing how nursery growers perceive automated and mechanized nursery technologies (ANTs) and determine how these perceptions relate to adoption. This information could guide the development of Extension programs that help nursery operations make informed decisions about ANT adoption and identify ANT characteristics that are positively correlated with ANT adoption. This document was designed for Extension professionals and other practitioners who serve nursery grower clientele across the United States, including companies developing and marketing ANTs to nursery operations. Written by Laura A. Warner, Alicia L. Rihn, Amy Fulcher, Susan Schexnayder, Anthony V. LeBude, Lloyd Nackley, Margarita Velandia, and James Altland. https://edis.ifas.ufl.edu/wc425